The TV studio production handbook - Brown, Lucy; Duthie, Lyndsay (I.B. Tauris, 2016)
This book explains the production process from beginning to end and covers everything media students need to know to create a successful studio television programme. The book is packed with interviews from top TV executives from the UK, USA, Australia, and China and includes live case studies and scripts from hit international formats covering every genre. Spanning from reality, to drama, to news, with scripts from Britain's Got Talent, Big Brother, Coronation Street, The Chase, Teletubbies, Channel 4 News and more. The authors, both award-winning TV programme-makers and academic programme leaders, break things down genre by genre and explore pre-production, casting, scripting, as well as all the required paperwork, from call sheets to running orders. They also examine the future of studio and the multiplatform opportunities available for programme makers internationally.